Effects of F-Number on the Histotripsy Intrinsic Threshold and Cavitation Bubble Cloud Behavior - Vlaisavljevich, Eli (Phys Med Biol, 2016)
Histotripsy is an ultrasound ablation method that depends on the initiation of a cavitation bubble cloud to fractionate soft tissue. Although previous work has provided significant insight into the process of intrinsic threshold histotripsy, the majority of these studies have used highly focused (i.e. f-number<0.6) transducers. In this study, we investigate the effects of f-number on the histotripsy intrinsic threshold and cavitation bubble cloud behavior using a 500 kHz array transducer, with the effective f-number of the transducer varied from 0.51 to 0.89. The intrinsic threshold did not significantly change with f-number, with the threshold remaining ~27–30 MPa for all conditions. The predictability of intrinsic threshold histotripsy was further demonstrated by experiments comparing the predicted and experimentally measured bubble cloud dimensions, with results showing close agreement for all f-numbers. Finally, the effects of f-number on “bubble density” and tissue fractionation efficiency were investigated, with results supporting the hypothesis that the density of the bubbles within the bubble cloud significantly decreases at higher f-numbers, resulting in decreased fractionation efficiency. Overall, this study provides significant insight into the effects of f-number on intrinsic threshold histotripsy that will help to guide the development of intrinsic threshold histotripsy for specific clinical applications.